High-Tech Babies : The Debate Over Assisted Reproductive Technology - Winkler, Kathleen (USA Enslow Publishers, 2006)
Describes the techniques available to help infertile couples reproduce, including intrauterine insemination, in vitro fertilization, and surrogacy, as well as methods that may be available in the future.
Include Color Illustrations and Index
Keywords: Medical ethics